Migration and the crimes of People smuggling and trafficking. Technical-legal analysis - Laidiana Torres Rodríguez; Lisett D. Páez Cuba; Liliana Margarita Martínez Hernández (Technium Social Sciences Journal, 2021)
In this paper, a technical and legal analysis of the crimes of people trafficking and smuggling associated with migration was made, according to the mistaken regulations in the Cuban Penal Code. For that reason theoretical and empirical methods were used. A proposal for improving the regulation of the crimes of people trafficking and smuggling associated with it in the Cuban Penal Code was established, in order to a future amendment. It was analyzed the migration as a social phenomenon with a lot of legal and criminal consequences. In addition, the crimes of people trafficking and smuggling associated with it were defined and compared; and it was made a study from the comparative law about the regulation of these crimes in the foreign legislations.